Assessment of genetic variability in oat (Avena sativa L.) germplasm using agro-morphological traits and microsatellite markersParameshwaran Mathavaraj1, Prasanta Kumar Goswami1, Seuji Bora Neog2 and Akhil Ranjan Baruah3 - Parameshwaran Mathavaraj1, Prasanta Kumar Goswami1, Seuji Bora Neog2 and Akhil Ranjan Baruah3 (Electronic Journal of Plant Breeding)
This study assessed genetic variability among oat genotypes for twelve traits, including yield. Significant differences were found across all traits, with high heritability and genetic advance for the number of effective tillers, 1000-seed weight, and grain yield. Hierarchical clustering using morphometric traits grouped the genotypes into four distinct clusters. We identified 665 potential microsatellites using 1000 contigs from NCBI and designed possible primer pairs to develop PCR-based markers in orphan crop like oats. Validation with a panel of 31 diverse genotypes revealed that seven of ten newly developed markers detected expected alleles, with four being polymorphic. Additionally, eight reported SSRs were used to assess genotypic differences. The markers showed a mean allele richness of 2.86 (range: 2-4) and a mean polymorphism information content (PIC) of 0.37 (range: 0.15-0.96). Cluster analysis indicated three distinct clusters with a mean dissimilarity of 0.54, demonstrating the markers’ effectiveness for genetic diversity assessment and breeding.